Health communication campaigns to drive demand for evidence-based practices and reduce stigma in the HEALing communities study. (1st December 2020) - Lefebvre, R. Craig; Chandler, Redonna K.; Helme, Donald W.; Kerner, Robin; Mann, Sarah; Stein, Michael D.; Reynolds, Jennifer; Slater, Michael D.; Anakaraonye, Amarachi R.; Beard, Dacia; Burrus, Olivia; Frkovich, Jenna; et al.
Highlights: We describe communication campaigns in an intervention to reduce opioid deaths. The community-engaged model includes three phases. Five campaigns will focus on naloxone, MOUD, and stigma reduction. Community surveys and fidelity measures gauge process and impact. Our model could help communities address other public health issues. Abstract: Background: The HEALing Communities Study (HCS) is testing whether the Communities that Heal (CTH) intervention can decrease opioid overdose deaths through the implementation of evidence-based practices (EBPs) in highly impacted communities. One of the CTH intervention components is a series of communications campaigns to promote the implementation of EBPs, increase demand for naloxone and medications for opioid use disorder (MOUD), and decrease stigma toward people with opioid use disorder and the use of EBPs, especially MOUD. This paper describes the approach to developing and executing these campaigns. Methods: The HCS communication campaigns are developed and implemented through a collaboration between communication experts, research site staff, and community coalitions using a three-stage process. The Prepare phase identifies priority groups to receive campaign messages, develops content for those messages, and identifies a "call to action" that asks people to engage in a specific behavior. In the Plan phase, campaign resources are produced, and community coalitions develop plans to distribute campaign materials. During the Implement stage, these distribution plans guide delivery of content to priority groups. Fidelity measures assess how community coalitions follow their distribution plan as well as barriers and facilitators to implementation. An evaluation of the communication campaigns is planned. Conclusions: If successful, the Prepare-Plan-Implement process, and the campaign materials, could be adapted and used by other communities to address the opioid crisis. The campaign evaluation will extend the evidence base for how communication campaigns can be developed and implemented through a community-engaged process to effectively address public health crises.